A comparative assessment of Greek universities' efficiency using quantitative analysis - Katharaki, Maria; Katharakis, George (International Journal of Educational Research, 2010)
In part due to the increased demand for higher education, typical evaluation frameworks for universities often address the key issue of available resource utilisation. This study seeks to estimate the efficiency of 20 public universities in Greece through quantitative analysis (including performance indicators, data envelopment analysis (DEA) and econometric procedures). The findings show inefficiency in terms of human resources management while also identifying a clear opportunity to increase research activity and hence research income. In addition to the immediate findings, this paper more broadly discusses the methodology behind the evaluation process used in this investigation and its potential to more consistently and reliably evaluate the efficiency of resource management by public universities. This paper is set against, and hopes to contribute to, the broader debate on reforming the management and administration system of Greek universities. © 2010 Elsevier Ltd.